Tuntunan Sholat Berbasis Android Studio: Aplikasi Untuk Siswa Madrasah Aliyah Negeri 2 Mojokerto - RODLI, MOH.; Pratitis Yusuf, Yulia; Widiastutik, Trisya (Inovasi: Jurnal Diklat Keagamaan, 2025)
The development of information and communication technology, particularly in the form of Android-based devices, has permeated various aspects of daily life. The use of smartphones is increasingly widespread and easily accessible to many people, including Madrasah Aliyah students. Seeing this phenomenon, the development of Android-based praying guidance media can be an effective solution to help students understand and carry out praying correctly. The research carried out is Research and Development (R and D), and the research procedure is analyzing by conducting needs surveys, designing prototypes, developing materials, validating experts and teachers, revising, implementing by testing materials, revising, evaluating, and getting products, and getting the final product using the ADDIE model. The instruments in the needs survey are questionnaires, interview guides, and field notes. Based on these findings, various praying guidances were developed. There are 7 types of praying performed, consisting of 4 fardhu prayings and 3 sunnah prayings. The final product produced is an Android Studio Based Praying Guidance Application for Madrasah Students (SI NASSHWA). This is one quick way to learn fardhu and sunnah prayings. This also trains students' honesty. Besides, the total percentage of student responses was 55.52%. It’s mean that student response belong to positive category. For other researchers conducting similar research are advised to conduct further studies to develop an Android-based praying guidance or conduct an evaluative study of this prototype product after it has been implemented for Madrasah Aliyah’s students.